Wind structure influence on pressure coefficient distribution on the surface of circular cylinder of the diameter 20 cm - Lipecki, Tomasz; Bęc, Jarosław; Błazik-Borowa, Ewa (Budownictwo i Architektura / Civil and Architectural Engineering, 2012)
The paper deals with results and analyses of the model investigations which were performed in wind tunnel and were focused on the flow around single circular cylinder. Presented results are related to variations in the distribution of the normalized mean pressure coefficient on the surface of the model as well as its standard deviation. Sic cases of the approaching flow were taken into consideration. The flow was described by vertical profile of the mean wind speed, vertical profile of the intensity of turbulence, and power spectral density functions. The height and dimension of the model were respectively equal: H = 100 cm, D = 20 cm. Selected results of measurements have been shown in the paper as the effect of these experiments.